2013
DOI: 10.1039/c3ob41837e
|View full text |Cite
|
Sign up to set email alerts
|

Triazole biotin: a tight-binding biotinidase-resistant conjugate

Abstract: The natural amide bond found in all biotinylated proteins has been replaced with a triazole through CuAAC reaction of an alkynyl biotin derivative. The resultant triazole-linked adducts are shown to be highly resistant to the ubiquitous hydrolytic enzyme biotinidase and to bind avidin with dissociation constants in the low pM range. Application of this strategy to the production of a series of biotinidase-resistant biotin-Gd-DOTA contrast agents is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…utilized the advantage of rigid triazole linkers for designing and synthesis of their biotinidase-resistant biotin-Gd-DOTA contrast agents. 19 They have synthesized contrast agents conjugated with biotin via a triazole linkers generated by azide-alkyne cycloaddition. These rigid conjugates are excellent isosteres for similar biotin-amide contrast agents.…”
Section: Click Chemistry In Synthesis Of Mri Contrast Agentsmentioning
confidence: 99%
“…utilized the advantage of rigid triazole linkers for designing and synthesis of their biotinidase-resistant biotin-Gd-DOTA contrast agents. 19 They have synthesized contrast agents conjugated with biotin via a triazole linkers generated by azide-alkyne cycloaddition. These rigid conjugates are excellent isosteres for similar biotin-amide contrast agents.…”
Section: Click Chemistry In Synthesis Of Mri Contrast Agentsmentioning
confidence: 99%
“…We have previously demonstrated that a range of non-hydrolysable triazole derivatives of biotin show very strong binding to avidin, with K d values in the pM range. 17 In this instance, functional activity of the H4K12C triazole biotin adduct was demonstrated by Western blot using an anti-biotin antibody ( Fig. 2b ), and the assembly of histone complexes incorporating site-selective biotinylation is currently under investigation.…”
mentioning
confidence: 94%
“…This stems from a robust and green protocol for the synthesis of triazole derivatives. 33 In addition to metal sensors, triazole is extensively used in the synthesis of catalyst, 34 dendrimers, 35 biomolecule conjugates, 36 and metal organic frameworks. 37 BODIPY-triazole combinations were reported as uorescent chemosensors for the detection of metal ions, e.g.…”
Section: Introductionmentioning
confidence: 99%